Implementasi Fuzzy Analytical Hierarchy Process Untuk Menentukan Berita Utama (Headline News) di Kavling 10 - Akbar Imani Yudhaputra; Edy Santoso; Yuita Arum Sari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
News is very important for people's lives, through public news can add insight, get new or current information, express opinions or opinions in public etc. news can be published through a bulletin, in the bulletin there is a headline which is the best news from a collection of news that is there to be used as a headline for the purpose of attracting interest and increasing the curiosity of readers on the next page, so that the selection of headlines is very important. There are problems experienced by the Kavling 10 Editor for or in determining the headlines. There are two options prepared namely searching for the highest news value and preparing a special coverage theme. The two options still have a problem, which is the confusion of choosing the main news in a bulletin called Juros PKK Maba. The criteria used to look for the highest news value are 12, while the special coverage theme criteria are 6. With the Fuzzy Analytical Hierarchy Process (FAHP) method, the problem can be overcome. The FAHP procedure systematically or sequentially starts from determining the weight of the criteria, testing the consistency, determining the alternative weights for each criterion, and ranking so as to produce recommendations. Tests performed using the Spearman correlation test with a total of 8 tests resulted in values ​​of 0.64, 0.83, 0.61, 0.91, 0.65, 0.78, 0.64 and 0.78. So we get four strong relationships, three very strong relationships, and one close to perfect relationship. All test results have a direct relationship. It was concluded that the results of the ranking of the system using the FAHP method with the results of the ranking of experts there is a match.